THE EFFECT OF PROFITABILITY RATIO, SOLVABILITY RATIO, MARKET RATIO ON STOCK RETURN - Febria Nalurita (Business and Entrepreneurial Review, 2015)
This research performed in order to test influence of fundamental factor (ROA, DER and PER) on stock return both simultaneously and partially, on Property, Real Estate and Construction companies that listed in Indonesia Stock Exchange for period 2010-2014.Secondary data is used and collected based on time series and cross section from 2010 up to 2014. The total study sample was 38 Property, Real Estate and Construction companies that is determined through purposive sampling. The research uses panel data regression model and processed with the EVIEWS 9 program. Hausman test used in this study shows Random Effect Model (REM) as data estimation technique.The result of this research, the partial inferred Debt to Equity Ratio (DER)have significant effect on stock return. Return on Asset (ROA) and Price Earning Ratio (PER) don’t have significance effect on stock return. Result of this research indicate that fundamental factor performance Debt to Equity Ratio (DER) used by investor to predict stock return of Property, Real Estate and Construction companies that listed in Indonesia Stock Exchange at period 2010-2014.Simultaneously the fundamental factors Return on Assets (ROA), Debt to Equity Ratio (DER) and Price Earning Ratio (PER) significantly effect the stock return on the Property, Real Estate and Construction companies.The sample in this study only Property, Real Estate and Construction companies that only has a specification in the type of business sample firms, then the influence of the independent variables only describe the affect specifically on the Property, Real Estate and Construction sectors.